Bending behavior and influence parameter optimization of connection joints of disc-buckle type formwork support - Jinfeng Dong; Zelong Liao; Haiqing Liu; Zhongwei Zhao; Ming Lei; Zimu Chen; Liang Wang; Xiangen Gong (Scientific Reports)
Abstract In order to systematically study the bending behavior of the connection joints of the disc-buckle type formwork support, the accurate numerical model of the disc-buckle type connection joints was obtained through the experimental on the bending behavior of the connection joints of the disc-buckle type, and the bending moment-rotation curve of the joints was verified. The analysis of the failure mode and stress distribution of the joints reveals the importance of the bending behavior of each component. By establishing an accurate numerical model of the joint, the accuracy of the bending experiment of the joint was verified, and the parametric analysis of the influence factors such as the depth of the wedge insertion the disk-plate, the initial position of the wedge insertion the disk-plate, the thickness of the wedge, material constitutive of the wedge and the thickness of the disk-plate was carried out to grasp the influence of the relevant parameters on the bending behavior of the joint. The results shown that the connection joints of the disc-buckle type formwork support were a typical semi-rigid connection joints. The thickness of the disk-plate plays a decisive role in the joint bending capacity, and the optimum thickness of the disk-plate was 10 mm. The thickness of the wedge was proportional to the joint bending capacity, and the optimal thickness of the wedge was 7 mm. The drop depth of the wedge should not exceed 6 mm during the locking process and the most suitable yield strength of the wedge was set to 450–500 MPa.